2022
DOI: 10.1111/eci.13776
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin treatment against SARS‐CoV‐2: A randomized phase III study to evaluate the safety and efficacy of a pan‐protease inhibitor for moderate COVID‐19

Abstract: Background SARS‐CoV‐2 virus requires host proteases to cleave its spike protein to bind to its ACE2 target through a two‐step furin‐mediated entry mechanism. Aprotinin is a broad‐spectrum protease inhibitor that has been employed as antiviral drug for other human respiratory viruses. Also, it has important anti‐inflammatory properties for inhibiting the innate immunity contact system. Methods This was a multicentre, double‐blind, randomized trial performed in four Spanish hospitals comparing standard treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“… 4 More encouraging data came from the aprotinin study: aerosolized aprotinin reduced the length of hospital admission and oxygen requirement. 5 Importantly, no adverse reactions were observed. Thus, inhalation could be a safer way to administer protease inhibitors against COVID-19, tailored to reach TMPRSS2 that is expressed on the cell surface of target cells in the airways.…”
mentioning
confidence: 96%
“… 4 More encouraging data came from the aprotinin study: aerosolized aprotinin reduced the length of hospital admission and oxygen requirement. 5 Importantly, no adverse reactions were observed. Thus, inhalation could be a safer way to administer protease inhibitors against COVID-19, tailored to reach TMPRSS2 that is expressed on the cell surface of target cells in the airways.…”
mentioning
confidence: 96%
“…Effects against BA.2 were less pronounced (IC50: 1.95µM) but still in the range of clinically achievable plasma concentrations after systemic administration, which have been shown to reach 11.8µM 6 . Moreover, aerosol preparations like the one used in the clinical trial that demonstrated therapeutic efficacy of aprotinin against COVID-19 7 are expected to result in substantially higher local aprotinin concentrations in the lungs.…”
mentioning
confidence: 99%
“…Previously, we have shown that the protease inhibitor aprotinin inhibits replication of the SARS-CoV-2 original Wuhan strain at least in part by inhibition of the cleavage and activation of the viral spike (S) protein by host cell proteases [Bojkova et al, 2020]. Based on these findings, a clinical trial was initiated that reported improved outcomes of COVID-19 patients treated with an aprotinin aerosol [Redondo-Calvo et al, 2022]. Among other improvements, aprotinin treatment reduced the length of hospital stays by five days [Redondo-Calvo et al, 2022].…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, a clinical trial was initiated that reported improved outcomes of COVID-19 patients treated with an aprotinin aerosol [Redondo-Calvo et al, 2022]. Among other improvements, aprotinin treatment reduced the length of hospital stays by five days [Redondo-Calvo et al, 2022].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation